The Younger and The Deliberative Budgeting Process at Village Level - Sukarso; Dasuki, Niken Paramarti (Journal of Local Government Issues, 2025)
The village community has the prospect of embroiling in the budgeting process more than just being the target group or beneficiaries. Still, as a subject, it is deliberative budgeting. The study aims to explain how the deliberative budgeting process at the village level can be realized or optimized. This study operationalizes three main variables: perception, attitude, and commitment, controlled by the respondent's characteristics. By using an experimental approach in a village to determine changes in understanding after treatment and correlational analysis, it turns out that there are two things found. First, the post-test score is higher than the pre-test score, and second, the age associated with the commitment to participate was a negative correlation, both pre-test and post-test. This shows that changes in understanding or perception will result in changes in commitment to participate. Then, increasing knowledge of budgeting in the village is much more effective for the younger age group to be more involved in the budgeting process. Therefore, in conclusion, increasing understanding through socialization, training, or education on various matters, especially budgeting, will impact the commitment to be more involved for the younger age group compared to the older one. These results can complement the explanation of various findings on community participation in village policy formulation, especially budgeting.